Changes in Demand for Crude Oil and its Correlation with Crude Oil and Stock Market Returns Volatilities: Evidence from Three Asian Oil Importing Countries - Bouazizi, Tarek; Hadhek, Zouhaier; Mrad, Fatma; Lafi, Mosbah (International Journal of Energy Economics and Policy, 2021)
While different streams of literature exist investigating the relationship and the conditional correlation between oil import prices, oil returns volatility and stock market returns volatility. The period of the study runs from July 1997 until July 2017 with a monthly data. The objectives of the present paper are the following to investigate the order of the mean equation, the order (p,q) of the conditional variance and the order (r,s) of the Diag-BEKK model. Data from the Indian and Indonesian stock market returns series respectively shows the existence of appropriate ARMA(2,2)-EGARCH(2,2) and ARMA(2,2)-IGARCH(2,2) models. The appropriates models of Diag-BEKK(p,q) for China, India and Indonesia are Diag-BEKK(1,2), Diag-BEKK(0,2) and Diag-BEKK(0,2) respectively. In the three Asian Countries, the three variables are correlated. Also, equations show a statistically significant covariation in oil import price, which depends more on its lags than on past errors. Consequently, oil demand are influenced by past information which is common to the crude oil market and the stock market and to its volatilities. They suggest that the comovements of the three series display an extremely volatile trend for the study period. Keywords: Oil Volatility, Oil Import Price, Stock Market Volatility, Conditional Mean, Conditional variances, Simultaneous Equations Model, OLS. JEL Classifications: B26, C3, C58, D58, G15, Q41 DOI: https://doi.org/10.32479/ijeep.10650